GABAergic transmission in rat pontine reticular formation regulates the induction phase of anesthesia and modulates hyperalgesia caused by sleep deprivation. (27th March 2014) - Vanini, Giancarlo; Nemanis, Kriste; Baghdoyan, Helen A.; Lydic, Ralph
Abstract: The oral part of the pontine reticular formation (PnO) contributes to the regulation of sleep, anesthesia and pain. The role of PnO γ‐aminobutyric acid (GABA) in modulating these states remains incompletely understood. The present study used time to loss and time to resumption of righting response (LoRR and RoRR) as surrogate measures of loss and resumption of consciousness. This study tested three hypotheses: (i) pharmacologically manipulating GABA levels in rat PnO alters LoRR, RoRR and nociception; (ii) propofol decreases GABA levels in the PnO; and (iii) inhibiting GABA synthesis in the PnO blocks hyperalgesia caused by sleep deprivation. Administering a GABA synthesis inhibitor [3‐mercaptopropionic acid (3‐MPA)] or a GABA uptake inhibitor [nipecotic acid (NPA)] into rat PnO significantly altered LoRR caused by propofol. 3‐MPA significantly decreased LoRR for propofol (−18%). NPA significantly increased LoRR during administration of propofol (36%). Neither 3‐MPA nor NPA altered RoRR following cessation of propofol or isoflurane delivery. The finding that LoRR was decreased by 3‐MPA and increased by NPA is consistent with measures showing that extracellular GABA levels in the PnO were decreased (41%) by propofol. Thermal nociception was significantly decreased by 3‐MPA and increased by NPA, and 3‐MPA blocked the hyperalgesia caused by sleep deprivation. The results demonstrate that GABA levels in the PnO regulate the time for loss of consciousness caused by propofol, extend the concept that anesthetic induction and emergence are not inverse processes, and suggest that GABAergic transmission in the PnO mediates hyperalgesia caused by sleep loss. Abstract : The intravenous anesthetic propofol significantly decreases extracellular GABA levels in rat PnO. Pharmacologically increasing or decreasing extracellular GABA levels increases or decreases, respectively, the time to loss of consciousness caused by propofol. GABAergic transmission in the PnO does not modulate the resumption of consciousness after isoflurane‐ and propofol‐anesthesia. Administration of a GABA synthesis inhibitor into the PnO blocks the hyperalgesia caused by sleep deprivation.